Robust and Flexible Colloidal Photonic Crystal Films with Bending Strain–Independent Structural Colors for Anticounterfeiting. (27th February 2020) - Pan, Mengyao; Li, Xiao bai; Xiong, Chengjia; Chen, Xiaoyi; Wang, Lebin; Chen, Xi; Pan, Lei; Xu, Hongbo; Zhao, Jiupeng; Li, Yao
Abstract: Colloidal photonic crystals (PCs) possess iridescent and metallic structural color, making them an attractive candidate for anticounterfeiting. However, traditional colloidal PC‐based anticounterfeiting materials usually have bending‐induced color‐switching characteristics or poor flexible stability, significantly affecting their color reproducibility and durability. Here, a novel robust colloidal PC film with bending strain–independent structural color and high flexible stability has been developed through the self‐assembly of SiO2 particles into the poly(ethylene glycol) diacrylate (PEGDA) matrix. The unique microstructure of the colloidal PC film contains ordered and disordered arrays of SiO2 nanoparticles embedded into the flexible PEGDA matrix, which is crucial to achieving bending strain–independent structural color. In fact, during the bending process, the colorless disordered arrays act as the buffer space, avoiding deformation of the colored ordered arrays and thus maintaining its original structural color. Remarkably, the film retains its structural and optical integrity after 10 000 times bending, supporting its high flexible stability and robustness. In addition, the film shows high transparency so that it can easily achieve an invisible and visible state transition under switch of weak and strong light. The film is potentially useful for applications in anticounterfeiting and encryption. Abstract : A colloidal photonic crystal prepared by a photopolymerization process has bending strain–independent structural color, high transparency, and good durability. Therefore, it can retain original color when it undergoes bending deformation and achieves an invisible and visible state transition by changing the illumination intensity, making it an ideal material for anticounterfeiting purposes.